The Development of Byzantine Archaeology and Historiographical Tradition in Colonial Palestine, 1800-1948 - Reynolds, Daniel. author. (orcid)0000-0002-3194-4130 Link aut Link
XXIII, 144 p. 14 illus.
Keywords: “Dr. Daniel Reynolds offers a landmark study that reframes Byzantium’s legacy in the Eastern Mediterranean through the lens of colonial and postcolonial geopolitics. Meticulously documented and analytically rich, it offers essential insights into Byzantine, Levantine, and imperial histories. I strongly endorse this book.” —Anahita Motazed Rad, Visiting Senior Fellow, Department of International Relations, London School of Economics and Political Science, UK This book examines the relationship between the emergence of Byzantine archaeology and British colonialism during the period of the British Mandate in Palestine. Taking a single case study, the Negev Desert (now in southern Israel), this study explores how the development of Byzantine archaeology and historical enquiry in the region after 1800 provided the British government with a political and economic blueprint to secure its strategic interests over the Suez Canal. Several excavations of Byzantine sites during the British Mandate were utilised as an historic proof of concept for scientific programmes of ‘desert greening’, and to advocate for the displacement of Arab populations in favour of British economic development and town planning. Invariably, such contemporary concerns to secure British access to the Suez after 1869 shaped the interpretation of Byzantine history. Ideas of the Negev as a timeless ‘frontier zone’, which benefitted from the imposition of a central imperial government and increased economic immigration from a ‘Hellenised’ western Europe, gained a historical precedent in an imagined Byzantine past. Daniel Reynolds is Associate Professor in Byzantine History at the University of Birmingham, UK.